African cats [videorecording (DVD)] - Jackson, Samuel L. (Walt Disney Studios Home Entertainment, 2011)
Set against one of the wildest places on Earth, experience the extraordinary adventure of two families as they strive to make a home in an untamed land. Stunning high-definition, breathtaking images bring viewers face-to-face with the majestic kings of the savanna and their true-life love, humor, and determination. Blending family bonds with the power and majesty of the wild, it's an exciting, awe-inspiring, and heart-touching experience.